2016
DOI: 10.1007/s11060-016-2256-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic impact of immune modulatory molecule PD-L1 in meningioma

Abstract: While immunotherapy may offer promising new approaches for high grade meningiomas, little is currently known of the immune landscape in meningiomas. We sought to characterize the immune microenvironment and a potentially targetable antigen mesothelin across WHO grade I-III cases of meningiomas, and how infiltrating immune populations relate to patient outcomes. Immunohistochemistry was performed on tissue microarrays constructed from 96 meningioma cases. The cohort included 16 WHO grade I, 62 WHO grade II, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 30 publications
7
91
0
Order By: Relevance
“…Besides myeloid cells, we found that leukocyte infiltrate in meningioma biopsies contained also lymphocytes, constituted for the vast majority by T cells with almost 50% of CD8 C T cells, in line with previous results 18,19,23,24 and no differences were observed with tumor grading (data not shown), as shown by other studies. 19,24 However, in grade III meningiomas Du et al reported a significant decrease in the number of CD3 C T lymphocytes, both CD4 C and CD8 C , as compared to low-grade meningiomas, 23 thus suggesting that T cells are reduced in high-grade meningiomas.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Besides myeloid cells, we found that leukocyte infiltrate in meningioma biopsies contained also lymphocytes, constituted for the vast majority by T cells with almost 50% of CD8 C T cells, in line with previous results 18,19,23,24 and no differences were observed with tumor grading (data not shown), as shown by other studies. 19,24 However, in grade III meningiomas Du et al reported a significant decrease in the number of CD3 C T lymphocytes, both CD4 C and CD8 C , as compared to low-grade meningiomas, 23 thus suggesting that T cells are reduced in high-grade meningiomas.…”
Section: Discussionsupporting
confidence: 93%
“…The presence of tumor-associated macrophages in meningioma is in line with other studies. [14][15][16][17][18][19] Myeloid cells have been characterized by CD68 expression 14,19 together with CD14, HLA-DR and CD163 expression 15,17 and described as a heterogeneous population composed of round, oval, ameboid or ramified mononuclear cells with small, dense nuclei together with mononuclear cells with slight to marked vacuolation, 16 all morphologic characteristics that we found also in our cytospin evaluation. Differently from Domingues et al, 18 in our analyses we also observed a myeloid cell population with low expression of HLA-DR that morphologically corresponds to granulocytes.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Moreover, a recent study in which patients with urothelial cancer were treated with the anti-PD-L1 agent, atezolizumab, showed that PD-L1 expression on tumor immune infiltrate was associated with improved clinical responses [6]. Intriguingly, both high-grade meningioma and high-grade glioma show increased rates of PD-L1 expression, suggesting that PD-L1 may correlate both with tumor aggressiveness and potential response to therapy [39, 40]. However, additional studies have shown that patients with PD-L1 negative tumors may also exhibit clinical responses to anti-PD-1 therapies [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Within tumor cells, expression of PD-L1, the PD-1 receptor ligand, increases with WHO tumor grade (17,55,57,58). However, overall mRNA or protein levels, as analyzed by RT-PCR, ISH, IHC, and flow cytometry varies widely from study to study.…”
Section: Expression/immunoprofilingmentioning
confidence: 99%